PENGENDALIAN PERSEDIAAN KERTAS HVS PADA UD.EMPAT S DI SANGATTA - Rahmah, Dwi Noor (EKONOMIA, 2013)
The purpose of the study to determine the amount of paper supplies to be provided by Business Category Four S in the future datang.Penelitian held for 3 months ( April to June 2013) on Trade Effort Four S in Sangatta , which bekaitan with HVS paper on inventory control Trade Enterprises in Four S Sangatta.Kegiatan dilakukanyaitu research : A literature study , field observations , interviews , documentation , data collection and analysis . Dikupulkan data in the study include : a general overview of the company , organization structure and answers responden.Alat optimization of raw material inventory analysis of paper , using the model of Economic Order Quantity ( EOQ ) , with the following procedures : 1 ) . Calculate the optimal amount of inventory 2 ) . calculating storage costs per year : the average frequency - average 3 x storage costs ) . calculate the total annual cost : = cost + storage cost reservations 4 ) . To calculate optimal inventory EOQ happen if booking fee = cost penyimpanan.Metode used herein are comparative ( comparison ) where an order made by the company with the number of orders EOQ model . . Based on the analysis performed by means of analysis of the EOQ ( Economic oreder Quantity ) shows that the optimal inventory that occurred as much as 18 685 reams For reservations once the cost is Rp . 250,000 , booking fee per year is Rp . 980 968 with a frequency of booking as many as 4 times a year , with the amount of inventory each time ordering as many as 18 685 rim . Known to the cost of storage based on the analysis performed is Rp . 980 962 , - a year . It is the result of multiplying the average frequency multiplied by the cost of storage in the form of a percentage set by the company , in this case the company set at 0.5 % of value of goods . Price per ream of paper HVS is Rp . 21,000 the number of bookings once known as the rim 18 685 once the booking . Rp1.961.930 This number is the sum of the booking fee plus the cost of the calculation results penyimpanan.Berdasarkan company should book as much as 4 times a year with as many as 18 685 reams booking number once the booking . Total inventory is optimal inventory with a total cost of 1,961,930 , for a good period of reservation is for 52 working days per one booking Keywords : Control Pesediaan , EOQ